Judicial Review On The Authority Of National Institution In The Disbanding Of Community Organization Who Are Contradicting The 1945 Constitution Of The Republic Of Indonesia - Hassanain, Haykal; Negoro, Theo; Tiopan, Demson (Archives of Business Research, 2019)
A community organization who contradicts the constitution will obviously disturb the common order and also disturb the system of Indonesian people and the nation itself, especially if such organization aims to change the Indonesian constitution. In Chapter XVII of Law Number 17 of 2013 regarding Community Organization, later known as the Community Organization Law, it is stated that the disbanding of community organization must go through a procedure which consist of a warning, temporary suspension and then the disbanding by the court of law. In the Community Organization Law, the disbanding of an organization is done by a Judicative Institution which is through the decision of a judicial board. However, the Government Regulation in Lieu of Law Number 2 of 2017 regarding the Amendment on Law Number 17 of 2013 regarding Community Organization, later known as the Government Regulation in Lieu of Community Organization Law states that the disbanding of a Community Organization contradicting the constitution only goes through the administrative admonition, temporary suspension of activity, and later the revocation of listed certification or the revocation of lawful institution status by the Government. The purpose of this research is to discover the authority of National Institution in disbanding Community Organization that contradicts the 1945 Constitution of the Republic of Indonesia and also the authoritative obstacle faced by the national institution in dissolving such organizations. This research is a normative one which researched existing secondary data as a literary data supported by empirical data acquired from interview processes. Result of the research shows that the governmental institution which in this case are the Ministry of Law and Human Rights and Judicative Institution which in this case the Supreme Court has authority to disband Community Organizations that contradicts the 1945 Constitution of the Republic of Indonesia based on normative terms. However, in order to establish justice on said organization, the disbanding must be done by Judicative Institution so that it is more objective, but not by the Supreme Court, but by the Constitutional Court, due to the existence of Public Organizations being closely related to the Constitutional Right the way it is for the Political Parties. This research suggests that the disbanding of Community Organizations that contradicts the 1945 Constitution of the Republic of Indonesia should be done by the Constitutional Court, preceded by material check on the applicable positive law. Keywords: Authority; National Institution; Community Organization; Constitution